Impact of good agricultural practices on Malaysian cattle industry: a case of foot and mouth disease (FMD) - Mohamad, Abdullah; Hamzah, Hanny Zurina (Academia Industry Networks, 2020)
This paper examines the impact of good agricultural practices on cattle production during and after the foot and mouth disease (FMD) outbreak in Peninsular Malaysia. A total of 355 cattle farmers were surveyed across six states in Peninsular Malaysia from April to October 2018. Using the propensity score matching (PSM) technique with nearest neighbor approach results demonstrate that by implementing good agricultural practices, total production has significantly increased by RM13,253.48 per year. Due to the benefit offers, it is vital to encourage more cattle farmers to use good agricultural practice in order to reduce FMD impact and increase farm production.